(untitled) (Bangladesh Critical Care Journal, 2014)
Guillain- Barrè Syndrome is characterized by acute progressive symmetric limb weakness and areflexia. A 32 year old female presented with progressive ascending areflexic muscular weakness and bilateral lower motor neuron type of facial palsy. She had anorexia, nausea and upper abdominal pain for 2 weeks. The findings of motor nerve conduction study are consistent with acute inflammatory demyelinating polyradiculoneuropathy. She had elevated liver enzyme and positive immunoglobulin M antibody against hepatitis E in blood. Based on clinical features, laboratory findings and electrophysiological study, she was diagnosed as Guillain- Barrè Syndrome following hepatitis E. She was treated with intravenous immunoglobulin and recovered fully. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19973 Bangladesh Crit Care J March 2014; 2 (1): 48-49